2022
DOI: 10.1101/2022.08.08.503143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uremic toxin indoxyl sulfate induces trained immunityviathe AhR-dependent arachidonic acid pathway in end-stage renal disease (ESRD)

Abstract: Trained immunity is the long-term functional reprogramming of innate immune cells following exposure to various insults that results in altered responses towards a secondary challenge. Indoxyl sulfate (IS) is a potent uremic stimulus associated with inflammation in chronic kidney disease (CKD). However, the impact of IS on trained immunity remains unknown. Here, we find that IS induces trained immunity in monocytes via epigenetic and metabolic reprogramming, resulting in augmented cytokine production upon LPS-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…In vitro -↑ AhR-dependent arachidonic acid pathway-reprogramming monocytes [126] In vivo -Alteration of metabolic pathways, including tryptophan metabolism [127] Epigenetic In vivo…”
Section: Mitochondria Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro -↑ AhR-dependent arachidonic acid pathway-reprogramming monocytes [126] In vivo -Alteration of metabolic pathways, including tryptophan metabolism [127] Epigenetic In vivo…”
Section: Mitochondria Dysfunctionmentioning
confidence: 99%
“…Hopp et al showed a link between kidney damage, metabolic reprogramming, and the accumulation of UTs, where an alteration in tryptophan metabolism was associated with a deterioration in kidney function and the accumulation of UTs in an in vivo model of autosomal dominant polycystic kidney disease [127]. UTs also stimulate inflammation via an AhR-dependent reprogramming of arachidonic acid metabolism [126].…”
Section: Metabolic Reprogramming In the Aki-to-ckd Transitionmentioning
confidence: 99%